Literature review of concept of Rasayana therapy in shalakyatantra - Sagar S Kumbhar; Samta D Bhandari (Ayurline: International Journal of Research in Indian Medicine, 2026)
Rasayana therapy is crucial in the current era as mankind suffers from various diseases. It improves the normal functioning of the human body and enhances the standard of life. In Shalakyatantra, Rasayana therapy provides clarity to sense organs, making them stronger and preventing diseases. Eyes, the seat of alochaka pita and tarpakakapha which regulate physiological functions. As aging increases, tarpakakapha decreases, causing vatavruddhi and pitta dushti, leading to visual impairment. As Netra that is eyes other sense organ ear and nose are regulated by various dosha and Dhatu. Rasayana nourishes all seven dhatus, attaining rogaharatva and vyadhikshmatva. This study discusses the effects of Rasayana in aushadha, ahara, and vihara, preventing degenerative changes in eyes and reducing visual impairment.